Gambaran Karakteristik Ibu Hamil Dengan Kekurangan Energi Kronis (KEK) di Puskesmas Baturiti I - Ni Made Budiartini; Ni Ketut Somoyani; Listina Ade Widya Ningtyas; Asep Arifin Senjaya; Ni Komang Erny Astiti (Journal of Advanced Nursing and Health Systems Innovation, 2026)
Background -- Chronic Energy Deficiency (CED) in pregnant women remains a prevalent nutritional problem and can have serious impacts on both maternal and fetal health, including an increased risk of pregnancy and childbirth complications. Objectives – This study aimed to find out the characteristics of pregnant women with CED in Puskesmas Baturiti I. Methods – The sample was 40 pregnant women with CED at Puskesmas Baturiti I who were determined by total sampling technique. The data collected on March to April 2025. It was collected by questionnaire and conducted by univariate analysis Results – The results showed that pregnant women with CED at Puskesmas Baturiti Baturiti I were mostly in the ideal age range of pregnancy (85%), most had secondary education (40%), the majority of parity was primigravida (65%), half of the respondents had adequate economic status (50%) and the other half were inadequate (50%). Nutritional status before pregnancy was mostly in the good category (62.5%). Conclusion – This study produces new information to increase education related to important indicators of SEZ occurrence that are beneficial for all pregnant women, not only at the research site.